2004
DOI: 10.1023/b:jonb.0000039649.20015.0e
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Reading and Metacognition: Narcissism, not Actual Competence, Predicts Self-Estimated Ability

Abstract: In this paper, we examine the relationship between people's actual interpersonal sensitivity (such as their ability to identify deception and to infer intentions and emotions) and their perceptions of their own sensitivity. Like prior scholars, we find the connection is weak or non-existent and that most people overestimate their social judgment and mind-reading skills. Unlike previous work, however, we show new evidence about who misunderstands their sensitivity and why. We find that those who perform the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
122
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 39 publications
13
122
2
1
Order By: Relevance
“…Though the norm data for this test showed female advantage (ds = .30 and .38 for the long and short forms, respectively; Costanzo & Archer, 1989, 1993, subsequent studies have mainly shown negligible sex differences (Ames & Kammrath, 2004;Aube & Whiffen, 1996;Iizuka, Patterson, & Matchen, 2002;Woods, 1996). These weak results are to be expected if items with female-stereotypic and male-stereotypic content are tallied together in the test's total score.…”
Section: Female-relevant Versus Male-relevant Contentmentioning
confidence: 79%
“…Though the norm data for this test showed female advantage (ds = .30 and .38 for the long and short forms, respectively; Costanzo & Archer, 1989, 1993, subsequent studies have mainly shown negligible sex differences (Ames & Kammrath, 2004;Aube & Whiffen, 1996;Iizuka, Patterson, & Matchen, 2002;Woods, 1996). These weak results are to be expected if items with female-stereotypic and male-stereotypic content are tallied together in the test's total score.…”
Section: Female-relevant Versus Male-relevant Contentmentioning
confidence: 79%
“…We first measured participants' overconfidence by having them complete the geography task individually and compared their self perceived 12STATUS ENHANCEMENT ACCOUNT OF OVERCONFIDENCE performance to their actual performance (e.g., Ackerman, Beier, & Bowen, 2002;Ames & Kammrath, 2004;Jones, Panda, & Desbiens, 2008;Krueger & Mueller, 2002;Kruger & Dunning, 1999;Larrick et al, 2007;Moore & Small, 2007). We then paired participants in dyads, wherein they worked on the same geography task together.…”
Section: Studymentioning
confidence: 99%
“…The results of prior research are mixed. In some cases narcissism was unrelated or negatively related to emotion recognition skills (e.g., Ames & Kammrath, 2004;Marissen, Deen, & Franken, 2012;Jauk, Freudenthaler, & Neubauer, 2016). …”
Section: Narcissism and Eimentioning
confidence: 99%